Vaccination: a look at the social representations of Brazilian children - de Gaspi, Suelen; Magalhães Júnior, Carlos Alberto de Oliveira; Tracana, Rosa Branca; Schneider, Eduarda Maria; Carvalho, Graça S. (Frontiers in Public Health, 2024)
IntroductionThe pandemic caused by COVID-19 has accentuated the debate on the need for vaccination and called into question the need to increasingly bring this topic, which is widely disseminated in the scientific world, to school classes at all schooling phases. In this scenario, science education plays a key role in disseminating knowledge about the importance of vaccination and the impacting factors of a lack of immunization. In order to better understand this movement, it is necessary to understand the representations of individuals as a way of broadening paths to change this scenario.ObjectivesThis study aimed to identify and analyse Brazilian primary school children’s social representations of vaccination.MethodsUsing the free word recall technique, the term “vaccination” was applied to evoke children’s ideas. The analysis of co-occurrences of evocations permitted us to identify their representations’ centrality.ResultsThe results showed that the centralizing elements guiding these children’s social representations were “needle,” “pain,” and “health center.”ConclusionThese results show the need to prevent the phobia of needles that arises in the first vaccination experiences and reinforce the importance of discussing the subject of vaccination in science teaching. This issue is even more critical, given the spread and impact of “fake news” on social media. There is an increasing need to emphasize the importance of vaccination, not only as a factor of individual protection but also as a commitment to collective health. This study also showed that the school, as usual, must become an ally in tackling this reality with children and their families.